A Sn / CuO catalyst and its preparation method and application

By using a rod-shaped Sn/CuO catalyst synthesized by a one-pot precipitation method in electrocatalytic carbon dioxide reduction technology, the problems of high reaction overpotential and low product selectivity were solved, and efficient carbon dioxide reduction was achieved, with a Faraday efficiency of 91%.

CN115726002BActive Publication Date: 2025-04-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110987108.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-26
Publication Date
2025-04-18
Estimated Expiration
2041-08-26

AI Technical Summary

Technical Problem

The existing electrocatalytic carbon dioxide reduction technology has the problems of high reaction overpotential and low product selectivity, making it difficult to effectively utilize carbon dioxide.

Method used

A small amount of Sn-doped rod-shaped Sn/CuO catalyst was synthesized by a one-pot precipitation method to be used to prepare carbon monoxide by electrocatalyzing carbon dioxide reduction. The catalyst has high carbon monoxide Faraday efficiency.

Benefits of technology

Low reaction overpotential and high product selectivity are achieved, and the Faraday efficiency can reach 91%, effectively solving the problem of low product selectivity in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003231091040000011
    Figure HDA0003231091040000011
  • Figure HDA0003231091040000012
    Figure HDA0003231091040000012
  • Figure HDA0003231091040000021
    Figure HDA0003231091040000021
Patent Text Reader

Abstract

The present application discloses a Sn / CuO catalyst, a preparation method and an application thereof. The catalyst is a Sn-doped CuO catalyst, and the mass percentage of Sn in the catalyst is 5-7%. The application of the catalyst Sn / CuO of the present invention to the electrocatalytic reduction of CO2 to prepare CO is relatively novel. The preparation method of the catalyst of the present invention is simple and easy, the price of raw materials is relatively low, the selectivity of CO2 electroreduction to CO is high, and the Faraday efficiency can reach 91%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a Sn / CuO catalyst, a preparation method and an application thereof, and belongs to the technical field of electrochemical catalysis. Background Art

[0002] Since the Industrial Revolution in the 1760s, the total consumption of fossil fuels such as coal, oil, and natural gas has increased rapidly, resulting in excessive emissions of carbon dioxide, causing environmental problems such as global warming and rising sea levels. On the other hand, renewable energy sources such as wind energy, solar energy, and tidal energy are easily restricted by climate and region, making them difficult to be effectively utilized. If renewable electric energy can be converted into high-value-added chemicals and liquid fuels such as carbon monoxide and hydrocarbons in the form of chemical bonds through electrocatalytic CO2 reduction reaction (CO2RR), then the effective utilization of carbon dioxide can be achieved while reducing the concentration of carbon dioxide in the air.

[0003] However, the current electrocatalytic reduction of carbon dioxide still has problems such as high reaction overpotential and low selectivity for specific products due to the close thermodynamic redox potentials of different products. Therefore, it is urgent to find an effective catalyst to achieve a small reaction overpotential and high product selectivity and activity. Summary of the invention

[0004] The present invention aims to provide a rod-shaped Sn / CuO catalyst for preparing carbon monoxide by electrocatalytic reduction of carbon dioxide. The present invention adopts a one-pot precipitation method to synthesize a small amount of Sn-doped rod-shaped Sn / CuO catalyst for preparing carbon monoxide by electrocatalytic reduction of carbon dioxide. The catalyst has low raw material price, simple preparation process, and the prepared catalyst has high carbon monoxide Faraday efficiency.

[0005] According to one aspect of the present application, a catalyst is provided, wherein the catalyst is a Sn-doped CuO catalyst, wherein the mass percentage of Sn in the catalyst is 5-7%; wherein the mass of Sn is calculated as the mass of the Sn element. When the mass percentage of Sn in the catalyst is 5-7%, the Faraday efficiency of electrocatalytic reduction of carbon dioxide to prepare carbon monoxide is the highest.

[0006] The catalyst microstructure is a discrete rod-shaped structure, and the length of the rod is 200-300 nm.

[0007] According to another aspect of the present application, a method for preparing the catalyst is provided, which comprises mixing a solution containing a copper source and a tin source with a precipitant, heating it, allowing it to cool naturally to room temperature, filtering it, washing it, drying it, and synthesizing the catalyst by a one-pot precipitation method.

[0008] Optionally, the copper source is selected from at least one of copper sulfate and copper chloride;

[0009] The tin source is selected from at least one of stannous chloride and stannic chloride;

[0010] The precipitant is an inorganic base;

[0011] The inorganic base is selected from at least one of sodium hydroxide and potassium hydroxide.

[0012] Optionally, in the solution containing a copper source and a tin source, the concentration of the copper source is 0.0130 to 0.0136 mol / L, measured in terms of molar amount of the copper element;

[0013] The concentration of the tin source is 0.8-0.9 mmol / L, calculated as the molar amount of the tin element.

[0014] The mass ratio of the copper source to the tin source is 19:1 to 21:1.

[0015] Preferably, the mass ratio of the copper source to the tin source can be independently 19:1, 20:1, or 21:1;

[0016] Optionally, the heating temperature is 90-100° C. and the heating time is 3-7 hours.

[0017] Preferably, the heating temperature can be independently selected from 90°C, 95°C, 100°C;

[0018] Preferably, the heating time can be independently selected from 3 hours, 4 hours, 5 hours, 6 hours, and 7 hours;

[0019] Optionally, the concentration of the inorganic base is 0.98-1.02 mol / L.

[0020] Preferably, the concentration of the inorganic base can be independently selected from 0.98 mol / L, 1.0 mol / L, 1.02 mol / L;

[0021] The mass ratio of the inorganic base to the copper source is 0.5:1 to 0.7:1.

[0022] Preferably, the mass ratio of the inorganic base to the copper source can be independently selected from 0.5:1, 0.6:1, 0.7:1;

[0023] In the present invention, the inorganic alkali solution is slowly added, which is beneficial to Sn 2+ Fully doped into the copper oxide lattice.

[0024] According to another aspect of the present application, a method for preparing carbon monoxide by electrocatalytic reduction of carbon dioxide is provided, the method comprising using a working electrode loaded with a catalyst to electrocatalytically reduce carbon dioxide to prepare carbon monoxide, wherein the catalyst is selected from the above catalyst or a catalyst prepared according to the above method.

[0025] Optionally, the loading amount of the rod-shaped Sn / CuO catalyst on the working electrode is 0.995-1.005 mg / cm 2 ;

[0026] Preferably, the catalyst loading can be independently selected from 0.995 mg / cm 2 , 1.0mg / cm 2 、1.005mg / cm 2 .

[0027] Optionally, the method for making the working electrode comprises the following steps:

[0028] A naphthol solution is added to a solution containing a catalyst, and a mixed solution is formed by ultrasonication. The obtained mixed solution is coated on an electrode, and dried at 50-70° C. to obtain the working electrode.

[0029] Optionally, in the solution containing the catalyst, the solvent is selected from at least one of isopropanol and ethanol;

[0030] The electrode is selected from at least one of carbon paper and glassy carbon electrode.

[0031] Optionally, the mass volume ratio of the catalyst to the solvent is 5.1 to 5.3 g / L;

[0032] The volume ratio of the solvent to the naphthol solution is 23 to 25;

[0033] The mass concentration of the naphthol solution is 6-7%;

[0034] The ultrasonic time is 20 to 40 minutes.

[0035] The beneficial effects of this application include:

[0036] 1) The catalyst of the present application has cheap raw materials and a simple preparation method, and its activity can be adjusted by changing the preparation conditions.

[0037] 2) The present application is novel in that the Sn / CuO catalyst is used in the electrochemical carbon dioxide reduction reaction.

[0038] 3) The rod-shaped Sn / CuO catalyst prepared in the present application has high selectivity for electrocatalytic reduction of carbon dioxide to carbon monoxide, and the Faraday efficiency can reach 91%. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the SEM image of the Sn / CuO catalyst prepared in Example 1 of the present application.

[0040] Figure 2This is the X-ray powder diffraction pattern of the Sn / CuO catalyst prepared in Example 1 of the present application, wherein (a) is the X-ray powder diffraction pattern of CuO and SnCuO; (b) is an enlarged view of the CuO (002) crystal plane.

[0041] Figure 3 This is a polarization curve diagram of the Sn / CuO catalyst prepared in Example 1 of the present application under nitrogen and carbon dioxide atmospheres.

[0042] Figure 4 This is the Faraday efficiency diagram of the Sn / CuO catalyst product prepared in Example 1 of the present application.

[0043] Figure 5 This is a current density diagram of the Sn / CuO catalyst product prepared in Example 1 of the present application.

[0044] Figure 6 This is a statistical chart of the diameter size of the Sn / CuO catalyst prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0045] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0046] Unless otherwise specified, the raw materials in the examples of the present application were purchased through commercial channels, wherein sodium hydroxide was purchased from Sinopharm; stannous chloride dihydrate was purchased from Aladdin; copper sulfate pentahydrate was purchased from Damao; naphthol solution with a mass fraction of 6% was purchased from DuPont; and potassium bicarbonate solution was purchased from Sigma.

[0047] The analysis method in the examples of this application is as follows:

[0048] The instrument for the electrochemical performance test is: Shanghai Chenhua CHI600E electrochemical workstation, model CHI600E, manufacturer is Shanghai Chenhua.

[0049] The morphology characterization instruments of the catalysts were: field emission scanning electron microscope, model JSM-7800F (JEOL Ltd.);

[0050] The X-ray powder diffraction characterization instrument is ANAlytical X'pert Pro diffractometer with witha Cu Kα radiation source

[0051] The instrument used for ICP detection is: PerknElmer ICP-OES 7300DV inductively coupled plasma emission spectrometer (ICP).

[0052] Example 1 Preparation method of Sn / CuO catalyst

[0053] Dissolve 1.33g of copper sulfate pentahydrate and 0.065g of stannous chloride dihydrate in 400mL of water, then add 20mL of sodium hydroxide solution (1mol / L), heat to 95℃ in an oil bath, and react for 5 hours. Cool the solution, filter, wash with water, and dry in an oven at 60℃ for 8 hours to obtain Sn / CuO rod-shaped material. Named D-1 # .

[0054] Sample D-1 prepared in Example 1 # The Sn / CuO rod-shaped material was characterized by SEM. Figure 1 As shown in the figure, Sn / CuO is in the shape of uniformly distributed rods. Figure 6 The average rod diameter is 33nm and the length is about 200nm.

[0055] Sample D-1 prepared in Example 1 # X-ray powder diffraction pattern characterization, see Figure 2 ,From the X-ray powder diffraction pattern, we can see the shift of CuO(002) crystal plane, proving that Sn is successfully doped into the CuO lattice.

[0056] The mass fraction of Sn in the synthesized catalyst was measured by ICP and was 5.254%.

[0057] Example 2 Preparation of working electrode

[0058] (1) 5 mg of the Sn / CuO rod-shaped material prepared in Example 1 was dispersed in 960 μL of isopropanol solution, and 40 μL of nafion solution was added, followed by ultrasonication until the catalyst was evenly dispersed.

[0059] (2) Working electrode: Take 200 μL of the Sn / CuO catalyst mixture obtained in step (1) and apply it on the surface of hydrophobic carbon paper (area 1*1 cm 2 ), dried, and finally the catalyst loading on the electrode surface was 1 mg / cm 2 .

[0060] (3) The platinum sheet is the counter electrode and the reference electrode is the calomel electrode.

[0061] Test Example 1 Electrochemical Activity Test

[0062] For the working electrode obtained in Example 2, a cyclic voltammetry scan was first performed in a 0.5 mol / L KHCO solution under a CO atmosphere at a scan rate of 100 mV·s -1The scanning range is -1.8~0V (vs.RHE), and the scanning is 40 cycles. The role of this step is to clean the catalyst surface and play a certain role in activation. Then the polarization curve is tested in carbon dioxide atmosphere and nitrogen atmosphere to characterize the electrocatalytic reaction performance of the catalyst. The scanning speed is 10mV·s -1 , the scanning range is -1.8~0V. Then, a constant voltage test is carried out in a carbon dioxide atmosphere, gas chromatography (GC) detects gas phase products, and nuclear magnetic resonance detects liquid phase products. In the above scanning range, calomel electrode is selected as the reference electrode and Pt sheet is selected as the counter electrode.

[0063] Figures 3 to 5 The catalyst provided in Example 1, i.e., sample D-1 # Electrochemical performance test diagram. It can be seen from the figure that the catalyst synthesized in the present application has high carbon monoxide selectivity and activity.

[0064] Figure 3 For sample D-1 # Polarization curves of Sn / CuO catalyst in nitrogen and carbon dioxide atmospheres. The catalyst undergoes hydrogen evolution reaction in nitrogen atmosphere, while in carbon dioxide atmosphere, hydrogen evolution reaction and carbon dioxide reduction reaction occur simultaneously. Figure 3 , at the same potential, the difference in current density proves that the catalyst can effectively catalyze the carbon dioxide reduction reaction.

[0065] Figure 4 For sample D-1 # Faraday efficiency diagram of Sn / CuO catalyst products. The gas phase products are carbon monoxide and hydrogen, and the liquid phase product is formic acid. At a lower potential of -0.8V (vs. RHE), the Faraday efficiency of carbon monoxide of this material reaches 91%, which exceeds the carbon monoxide selectivity of most copper-based catalysts at this potential. In addition, in the entire test potential range, the Faraday efficiency of carbon monoxide is above 80%, indicating that the catalyst has a high carbon monoxide selectivity.

[0066] Figure 5 For sample D-1 # Product current density diagram of Sn / CuO catalyst. It can be seen that with the increase of overpotential, the current density of carbon monoxide, hydrogen and formic acid all show an increasing trend. In addition, the increasing trend of the current density of carbon monoxide is significantly higher than that of formic acid and hydrogen, which proves that with the increase of overpotential, the generation rate of carbon monoxide accelerates.

[0067] The reason why Sn doping improves the selectivity of CuO to produce carbon monoxide in electrocatalytic carbon dioxide is mainly due to the 2+ Donates some electrons to Cu 2+, which increases the electron density of the active center Cu, thereby increasing the electron donation capacity of the active center to the reactant carbon dioxide during the reaction, reducing the reaction energy barrier, and thus improving the reaction activity and selectivity.

[0068] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing carbon monoxide by electrocatalytic reduction of carbon dioxide, characterized in that: Using a working electrode loaded with a catalyst, carbon monoxide is produced by electrocatalytic reduction of carbon dioxide; The catalyst is a Sn-doped CuO catalyst, wherein the mass percentage of Sn in the catalyst is 5-7%, wherein the mass of Sn is calculated as the mass of the Sn element; The preparation method of the catalyst comprises mixing a solution containing a copper source and a tin source with a precipitant and heating the mixture to synthesize the catalyst.

2. The method according to claim 1, characterized in that: The catalyst microstructure is a discrete rod-like structure, and the length of the rod is 200-300 nm.

3. The method according to claim 1, characterized in that: The copper source is selected from at least one of copper sulfate and copper chloride; The tin source is selected from at least one of stannous chloride and stannic chloride; The precipitant is an inorganic base.

4. The method according to claim 3, characterized in that The inorganic base is selected from at least one of sodium hydroxide and potassium hydroxide.

5. The method according to claim 1, characterized in that In the solution containing the copper source and the tin source, the concentration of the copper source is 0.0130-0.0136 mol / L, calculated as the molar amount of the copper element; The concentration of the tin source is 0.8-0.9 mmol / L, measured in terms of molar amount of the tin element; The mass ratio of the copper source to the tin source is 19:1 to 21:

1.

6. The method according to claim 1, characterized in that The heating temperature is 90-100° C., and the heating time is 3-7 hours.

7. The method according to claim 3, characterized in that The concentration of the inorganic base is 0.98-1.02 mol / L; The mass ratio of the inorganic base to the copper source is 0.5:1 to 0.7:

1.

8. The method according to claim 1, characterized in that The catalyst loading on the working electrode is 0.995-1.005 mg / cm 2 .

9. The method according to claim 1, characterized in that: The method for preparing the working electrode comprises the following steps: Adding a naphthol solution to a solution containing a catalyst, ultrasonically forming a mixed solution, applying the obtained mixed solution on an electrode, and drying at 50-70° C. to obtain the working electrode; In the solution containing the catalyst, the solvent is selected from at least one of isopropanol and ethanol; The electrode is selected from at least one of carbon paper and glassy carbon electrode.

10. The method according to claim 9, characterized in that The mass volume ratio of the catalyst to the solvent is 5.1-5.3 g / L; The volume ratio of the solvent to the naphthol solution is 23-25; The mass concentration of the naphthol solution is 6-7%; The ultrasonic time is 20 to 40 min.

Citation Information

Patent Citations

  • Method for synthesizing carbon monoxide through electrochemical catalytic conversion of carbon dioxide

    CN114892203A